The Effect of Orlistat Administration in Change of Glycemic Control and Weight Loss of Obesity or Overweight Patients with Type 2 Diabetes Mellitus - Johan, Abu Rizal Dwikatmono; Dewanti, Linda; Putri, Anandia Nafisah; Pantoro, Benny Iswanto; Albab, Chabib Fachry; Hutauruk, Maria Marind Desrianti; Novitasari, Triana (Folia Medica Indonesiana, 2022)
Hightlight: • The effect of orlistat on glycemic control and weight loss in overweight or obese type 2 diabetes mellitus patients was determined • HbA1c and FPG level in overweight and obese type 2 diabetes mellitus patient can improved by orlistat as an adjuvant therapy. Abstract: Risk of Type 2 diabetes mellitus (T2DM) increases steadily with increasing overweight and obesity, and these two-health problems are emerging epidemics worldwide. Orlistat, a lipase inhibitor for weight loss drug, is often used in T2DM medication as adjuvant therapy, but effectiveness of the drug for improving glycemic control on T2DM patients is unclear. This study was to determine the effect of orlistat on glycemic control and weight loss in overweight or obese patients with T2DM. Term